PENGARUH KOMUNIKASI INTERPERSONAL DAN MOTIVASI INTRINSIK TERHADAP KINERJA PEGAWAI PADA PEMERINTAHAN KECAMATAN SIBOLGA KOTA - Mandai, Indri Meisara; Simamora, Fauziah Nur; Hasmawati, Tiurlina (Pusat Riset dan Inovasi Nasional, 2023)
The government of Sibolga Kota District has not yet had maximum performance in terms of the services provided to the community that have not been maximized. The basic cause is the existence of interpersonal communication barriers among employees and low employee morale because motivation within employees is also low. This study aims to determine and analyze the effect of interpersonal communication and intrinsic motivation on employee performance in the District Government of Sibolga Kota. The type of research used is descriptive correlational with a population of 68 people and is used as an object of observation. Data collection used a questionnaire with a Likert measurement scale. The results showed that interpersonal communication and intrinsic motivation variables can affect employee performance variables by 54.7%. Interpersonal communication and intrinsic motivation together or simultaneously have a positive and significant effect on employee performance. Where the value of Fcount is greater than the value of Ftable (45.363 > 3.11) Partially interpersonal communication has a positive and significant effect on employee performance Where the value of tcount = (2.515) > ttable (1.992), Partially intrinsic motivation is the most dominant influence on employee performance, meaning that the intrinsic motivation variable determines more to improve employee performance compared to interpersonal communication. Where is tcount = (4.441) > ttable (1.992). It is recommended that the leadership is expected to maintain good relations with staff so that communication and good performance are maintained